The Impact of Problem-Based Learning Models to Improve English Achievement at Middle-School 2 Karawang Barat - Efendi, Arini; Ariyani, Amra; Asma, Nurul (ETDC: Indonesian Journal of Research and Educational Review, 2022)
The goal of this article is to investigate whether using problem-based learning models can help middle-school students improve their English learning achievements. The type of research used is classroom action research, carried out in 3 cycles at SMPN 2 Karawang Barat. Each cycle consists of stages of planning, implementation, observation, and reflection. The techniques used are observation technique and test technique. The assessment instrument uses a test sheet and an observation sheet. The results showed that in cycle 1, the average score of 75-80 students can be compared significantly in cycle 2 with an increase in the average score of 80-90. Likewise, cycle 3 shows an increase in value of 90-100. In general, it can be concluded that there is an increase in English learning outcomes for students at SMPN 2 Karawang Barat after learning is carried out through the use of problem-based learning models. As a suggestion, the use of problem-based learning models can be used by teachers or educators to improve learning outcomes, especially in the field of English.